2020
DOI: 10.1021/acs.est.9b07646
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Behaviors of λ-MnO2 in Electrochemical Lithium Recovery: Key Limiting Factors and a Route to the Enhanced Performance

Abstract: Recently developed electrochemical lithium recovery systems, whose operation principle mimics that of lithium-ion battery, enable selective recovery of lithium from source waters with a wide range of lithium ions (Li + ) concentrations; however, physicochemical behaviors of the key componentLi + -selective electrodein realistic operation conditions have been poorly understood. Herein, we report an investigation on a λ-MnO 2 electrode during the electrochemical lithium recovery process with regards to the Li … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 61 publications
1
29
0
Order By: Relevance
“…2(a) offered that XPS Mn 2p region and an asymmetrical main of Mn 2p 3/2 peak in the presence of Mn 3+ and Mn 4+ (Fig. 2(b)), which in the present a multiplet splitting of the λ-MnO 2 spectrum with satellite peaks at 655 and 641 eV and it referred to MnO 6 octahedral body which is similar to the earlier studies [15,30].…”
Section: ■ Results and Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…2(a) offered that XPS Mn 2p region and an asymmetrical main of Mn 2p 3/2 peak in the presence of Mn 3+ and Mn 4+ (Fig. 2(b)), which in the present a multiplet splitting of the λ-MnO 2 spectrum with satellite peaks at 655 and 641 eV and it referred to MnO 6 octahedral body which is similar to the earlier studies [15,30].…”
Section: ■ Results and Discussionsupporting
confidence: 84%
“…65 V that is evidence for coinciding with the electrolyte apportionment and following the construction of solid electrolyte interphase (SEI) layer generation. In the anodic orientation, one peak of oxidation at 1.3 V signalize that attributable to the delithiation process from the lithiated manganese oxide matrices and the dissociation of Li 2 O [30][31].…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The electrodes, λ-MnO 2 and Ag, were converted to Li x Mn 2 O 4 and AgCl x (0 < x < 1) when Li + was captured from the concentrate ( Joo et al., 2020 ). The mechanism of Li + recovery through λ-MnO 2 was thoroughly investigated by Kim et al., finding that increasing the density of the electrode/electrolyte interface can increase lithium uptake ( Kim et al., 2020d ). Lithium can also be selectively removed and up-concentrated using other intercalation cathode materials, such as LiFePO 4 coupled with a silver counter electrode.…”
Section: Electrochemical Separations For Selective Recoverymentioning
confidence: 99%
“…The recovery capacities are strongly influenced by the current density, the lithium concentration in the source electrolyte, and the intercalation material crystal size. 34 The authors found enhancement of the overall lithium recovery by increasing the density of electrode/electrolyte interface.…”
Section: Operation Parametersmentioning
confidence: 98%
“…However, under operation conditions less mass of lithium can be recovered per gram of LiMn 2 O 4 the higher the applied current and the lower the lithium ion concentration. 34 …”
Section: Operation Parametersmentioning
confidence: 99%